Quis custodiet ipsos custodes? Despite evidence to the contrary, the American Economic Review concluded that all was well with its archive - B. D. McCullough (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In 2011, the Annual Report of the Editor of the American Economic Review reported that the journal's data-code archive was functioning well, and no changes were made to the archive rules. This was based on an audit of the archive that the Editor had commissioned. In point of fact, all was not well with the archive: the archive did not support the publication of reproducible research. The rules for the archive should have been changed and were not; thus the American Economic Review continued to publish articles that were not reproducible. The cause of reproducible research was set back many years. Currently it appears that the AER intends to reproduce articles prior to publication; this would be a horrible mistake.
Keywords: B40; 330; replication; reproducible research